Reação de clones de cajueiro comum à resinose. - Moreira, Renato Cesar (2011)
The cashew nut (Anacardium occidentale) represents a social and economic tradition in Brazilian northeastern as one of the most important source of income and labor for its people. The releasing of early-dwarf clones contributed to increase yield and nut and apple quality, allowing gain in profit by small growers, in spite of increase genetic vulnerability of orchards. Cashew gummosis is presently the most important disease of this species in semi-arid regions of northeast. This study aimed to evaluate reactions of common selected clones of cashew to gummosis under high disease pressure of semi-arid region. Twenty clones selected by the cashew breeding program of Embrapa Agroindústria Tropical were evaluated for three consecutive years. Clones named CNPAT 06, CNPAT 08, CNPAT 11, CNPAT 12 and CNPAT 13 attained the highest levels of resistance, while CNPAT 07, CNPAT 09, CNPAT 14, COMUM 05 and COMUM 31 otherwise were the most susceptible ones. It was also found that clones CNPAT 08, CNPAT 11 and CNPAT 15 are able to heal gummosis cankers, which points to a new kind of resistance to be considered. Finally, it was shown that monitoring gummosis incidence it is possible to estimate disease severity.